1996
DOI: 10.1523/jneurosci.16-17-05478.1996
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Growth, Reactivity, and the Target of the Antiproliferative Antibody, TAPA

Abstract: Reactive astrocytes form a scar after injury to the CNS that many investigators believe contributes to the lack of functional regeneration. In the present study, we identify an astrocytic membrane protein that appears to play an important role in reactive gliosis and scar formation. Cultures of rat astrocytes were used as a model system to produce and to screen monoclonal antibodies that would alter cell growth. One antibody, AMP1, was identified that depresses the mitotic activity of cultured glial cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 49 publications
3
71
2
Order By: Relevance
“…16,17 ) and astrocyte lineages (GFAP, TAPA-1, CD44; refs. [18][19][20]. In addition, approximately one-third of GFP -cells expressed markers associated with neural progenitors and stem cells, including nestin 21 , prominin-1 (ref.…”
Section: Non-granule Cell Precursors Proliferate In Response To Bfgfmentioning
confidence: 99%
“…16,17 ) and astrocyte lineages (GFAP, TAPA-1, CD44; refs. [18][19][20]. In addition, approximately one-third of GFP -cells expressed markers associated with neural progenitors and stem cells, including nestin 21 , prominin-1 (ref.…”
Section: Non-granule Cell Precursors Proliferate In Response To Bfgfmentioning
confidence: 99%
“…These cellular membranes can then contract and cause secondary retinal detachments. The reactive glial responses and the proliferation of non-neuronal cells can have serious consequences, including loss of sight.Studies in our laboratory have identified a protein, CD81, which plays a role in the response of the brain [9], spinal cord [5], and retina [10]. We originally called CD81 the target of the antiproliferative antibody.…”
mentioning
confidence: 99%
“…We have hypothesized that this CD81 molecular complex is a key element in the contact inhibition between glial cells in the brain. Antibodies directed against CD81 depress the mitotic activity of cultured cells [9,17]. Furthermore, CD81 is expressed by glial cells in the brain during the second postnatal week, a time when their mitotic activity is down-regulated [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations